Cicero and Sallust: Debating Death - Woodman, A. J. (Histos, 2021)
This paper argues that the fate of the imprisoned Catilinarian conspirators was discussed not only at the famous meeting of the senate on 5 December 63 BC but also at an earlier meeting held on the previous day. The hypothesis of an earlier discussion seems to explain both the seemingly problematic nature of Cicero’s Fourth Catilinarian and the transmitted text of Sallust’s introduction to the famous debate.